2014
DOI: 10.1016/j.ibmb.2014.06.004
|View full text |Cite
|
Sign up to set email alerts
|

CutProtFam-Pred: Detection and classification of putative structural cuticular proteins from sequence alone, based on profile Hidden Markov Models

Abstract: The arthropod cuticle is a composite, bipartite system, made of chitin filaments embedded in a proteinaceous matrix. The physical properties of cuticle are determined by the structure and the interactions of its two major components, cuticular proteins (CPs) and chitin. The proteinaceous matrix consists mainly of structural cuticular proteins. The majority of the structural proteins that have been described to date belong to the CPR family, and they are identified by the conserved R&R region (Rebers and Riddif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
108
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(118 citation statements)
references
References 55 publications
4
108
0
Order By: Relevance
“…A search of the insect genome databases using these five M. sexta CPAP1 proteins identified presumptive orthologs in several insect genomes, including T. castaneum, and D. melanogaster. Similar results were independently obtained recently (Ioannidou et al, 2014). Therefore, five new groups including these proteins (named CPAP1-K to CPAP1-O) were created.…”
Section: Phylogenetic Analysis Of Chitin-binding Domainssupporting
confidence: 76%
See 1 more Smart Citation
“…A search of the insect genome databases using these five M. sexta CPAP1 proteins identified presumptive orthologs in several insect genomes, including T. castaneum, and D. melanogaster. Similar results were independently obtained recently (Ioannidou et al, 2014). Therefore, five new groups including these proteins (named CPAP1-K to CPAP1-O) were created.…”
Section: Phylogenetic Analysis Of Chitin-binding Domainssupporting
confidence: 76%
“…CPAP1s and CPAP3s) are highly conserved across several orders of insects (Ioannidou et al, 2014;Jasrapuria et al, 2010;Willis et al, 2012). Functional studies of multiple CPAPs in T. castaneum by RNAi have shown that CPAPs play essential nonredundant roles in T. castaneum (Jasrapuria et al, 2012).…”
Section: Origin and Evolution Of Cbds In Cpapsmentioning
confidence: 99%
“…Many CPs can be classified by the conserved sequence motifs they contain (Ioannidou et al ., 2014; Willis et al ., 2012). The largest group is known as CPs with the Rebers and Riddiford motif (CPR) that contain a core 28 amino acid sequence that is now recognized as part of a larger 63 amino acid consensus sequence (pfam00379) (Rebers and Riddiford, 1988; Willis et al ., 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Many of the insect structural CPs have been classified into 12 different families as defined by unique amino acid sequence motifs characteristic of each of the families (Willis, 2010;Ioannidou et al, 2014). The largest family is the CPR family whose members contain the Rebers & Riddiford (R&R) Consensus (Rebers and Riddiford, 1988).…”
Section: Introductionmentioning
confidence: 99%